CARCASS STUDIES IN NATIVE DUCKS REARED UNDER DIFFERENT HOUSING SYSTEMS - Gautham Kolluri; N. Ramamurthy; R. Richard Churchil; A. Sundaresan; G. Gawdaman (Indian Journal of Veterinary and Animal Sciences Research, 2024)
With the aim to examine the effect of rearing systems on major meat quality traits in native ducks, appropriate experimental investigation was conducted. Research material included a total of 160 day-old native ducklings. The experiment was organized in two treatments with two replications each. Two different rearing systems were employed the intensive (cages) and extensive system (free-range). The native ducklings belonging to same hatch were procured from a local duck farmer and reared simultaneously for a period of ten weeks. Twelve ducks (six male and six female) from each treatment were chosen randomly and slaughtered at the end of rearing period to study meat quality traits in native ducks. Differences were significant (P